JURNAL PENGARUH PENGGUNAAN MODEL PEMBELAJARAN JIGSAW TERHADAP KARAKTER SISWA DI KELAS XI SMA NEGERI 6 PADANGSISIMPUAN - Emmi Juwita Siregar (Institut Pendidikan Tapanuli Selatan, 2019)
The study aims to see how far the picture is whether there is a significant influence through the use of the Jigsaw Learning Model on the Character of Class IX Students of SMA Negeri 6 Padangsidimpuan 6. Research has carried out during April-June 2019 at SMA Negeri 6 Padangsidimpuan. Research method has been applied is the experimental method. The population that has been used in this study is all students of class XI 6 Padangsidimpuan State High School as many as 1 class, totaling 31 people. Sampling technique used is total sampling, where the total population is 31 people. In accordance with the results of the calculation of descriptive analysis, the value of the Jigsaw Learning model is 88.84 included in the